Socioeconomic Contribution of Oxytenanthera abyssinica (A.Rich) Munro and Determinants of Growing in Homestead Agroforestry System in Northern Ethiopia - Gebramlak, Girmay Darcha; Abadi, Nigussie; Hizikias, Emiru Birhane (Ethnobotany Research and Applications, 2016)
Oxytenanthera abyssinica (A.Rich.) Munro is known to be one of the lowland perennial grass species in Ethiopia with tremendous products and ecological services. It is uncommon to find O. abyssinica at the homestead as it was commonly found in the study area as part of an agroforestry system. This study was conducted to assess socioeconomic benefits of O. abyssinica and factors that influence farmers’ decision to use homestead agroforestry systems, based on a survey of 153 households in Serako kebele, Tselemti woreda, Ethiopia. This paper evaluates, using descriptive statistics, propensity score matching and logit regression analysis. The analysis demonstrates that farmers make decisions to grow O. abyssinica as homestead agroforestry systems based on household and field characteristics. The factors that significantly influenced growing decisions include homestead land holding size, total livestock owned, extension advice, and distance to local market. The average treatment effect (ATT) results show that the households with an O. abyssinica grower had significantly higher annual household income, annual expenditure, and number of months with enough food when compared to the control group. Therefore, we conclude that development of infrastructures that link producers with consumers, availability of large homestead land size, and expansion of extension facilities may enhance engagement of domestication of O. abyssinica at the homestead for sustainable livelihood options.